Bioactive fraction isolated from Curcuma angustifolia rhizome exerts anti-diabetic effects in vitro, in silico and in vivo by regulating AMPK/PKA signaling pathway - P. Kavya; M. Gayathri (Frontiers in Pharmacology)
Curcuma angustifolia Roxb. is a therapeutic herb and a member of the Zingiberaceae family. A potential bioactive fraction was isolated from the methanolic extract of Curcuma angustifolia rhizome using column chromatography, and it was characterised using 1H-NMR, GCMS and FTIR analyses. The bioactive fraction showed no toxic effects on the HepG2 cell line and it demonstrated inhibition of α-amylase and α-glucosidase enzymes in vitro with IC50 values of 2.75 ± 0.09 and 4.9 ± 0.07 µM, respectively. Molecular docking analysis also showed that nerolidol, the major constituent of the bioacive fraction inhibits α-amylase and α-glucosidase enzymes competitively, supporting in vitro antihyperglycemic activity. ADMET analysis showed that nerolidol has the necessary physicochemical parameters for drug-likeness. It also complies with Lipinski’s rule, indicating that its chemical structure is appropriate for designing safe and bioavailable oral drug. The antidiabetic efficacy of the isolated bioactive fraction was validated in type 2 diabetic albino wistar rats induced with a high-fat diet and a low dose (35 mg/kg bw) of streptozotocin. After 28 days of intervention, the lower and higher doses of the bioactive fraction (100 and 200 mg/kg BW) substantially decreased fasting blood glucose levels and ameliorated hyperglycemia, glucose intolerance, insulin resistance, and hyperlipidemia. The higher dose of bioactive fraction significantly ameliorated liver, kidney, and lipid profiles compared to the standard drug metformin and exhibited lower toxicity in the liver, kidney, pancreas, and epididymal adipose tissue than the lower dose of the bioactive fraction. Gene expression studies revealed that the bioactive fraction upregulated AMPK through downregulating PKA, a mechanism similar to the action of metformin. The results indicate that the isolated bioactive fraction could be a natural alternative to synthetic antidiabetic medications.